Appearance of an ensemble solitary pulse train in transient backward stimulated Raman scattering - Thang, Nguyen Manh (Communications in Physics, 2016)
A self-similarity approximation model for three-wave resonant interaction in transient backward stimulated Raman scattering (BSRS) was derived. Interestingly, as its asymptotic solution, the train of solitary backward Raman pulse train is possibly formed. This result can be considered as an increment of “single” soliton observed previously [A. Abdolvand et al., Phys. Rev. Lett 103, 183902 (2009)].